1997
DOI: 10.3109/10641969709080824
|View full text |Cite
|
Sign up to set email alerts
|

Vasodepressor Effects of Exercise are Accompanied by Reduced Circulating Ouabainlike Immunoreactivity and Normalization of Nitric Oxide Synthesis

Abstract: Our object was to evaluate the effects of regular mild exercise on blood pressure and on circulating level of ouabainlike factors (OLF) and of nitrate anion, an endproduct of nitric oxide (NO) in humans. We measured plasma ouabainlike immunoreactivity (OLI) and nitrate ions (NO3.) before and after mild exercise for 3 months' duration in 16 patients with essential hypertension, diabetes mellitus, obesity, or hyperlipidemia. Plasma OLI was measured using an amplified ELISA system with anti-ouabain antibody and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…the operation. Before operation, plasma OLI levels in this patient were within the reference interval of normal volunteers (41.4 ± 13.4 pg/ml) (10). Plasma levels of OLI increased during the operation, and peaked when the tumor was mechanically pressed for excision.…”
Section: Resultssupporting
confidence: 50%
“…the operation. Before operation, plasma OLI levels in this patient were within the reference interval of normal volunteers (41.4 ± 13.4 pg/ml) (10). Plasma levels of OLI increased during the operation, and peaked when the tumor was mechanically pressed for excision.…”
Section: Resultssupporting
confidence: 50%
“…However, the plasma levels of ouabain-like immunoreactivity (0.019 nmol/L = 12 pg/mL) in their study were almost equal to the findings (9 pg/ mL) in our previous enzyme-linked immunosorbent assay (ELISA) [13,20] and LC/MS analysis [12]. Binding proteins for EDLFs have been reported by Schoner's group and by us, and the activity of these proteins may of course affect the results of the assay [21,22].…”
Section: Discussionsupporting
confidence: 52%
“…The minimum detection limit was defined as the sample concentration resulting in a peak area of three times the noise level, and it was 1 ng/mL. When 1 to 100 ng/mL of MBG and TCB were used as a quality control sample Table 3 The chemical shift values of TCB in 13 The vacant columns represent the places where no chemical shift values could be detected. The structure and carbon numbers correspond to those shown in Fig.…”
Section: Lc/ms Analysis Of Mbg and Tcb In The Human Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed ambiguous results. An increase 9 as well as a decrease of plasma concentrations of ouabain-like compounds (OLCs) 10,11 have been reported. Here, we investigated the effect of physical exercise on the endogenous ouabain plasma concentration in several experimental settings as well as the influence of ␤-blockade and angiotensin-converting enzyme (ACE) inhibition.…”
mentioning
confidence: 99%